KEBIJAKAN PEMERINTAH TENTANG LEMBAGA KEUANGAN SYARIAH ERA REFORMASI - Itang Itang (AHKAM : Jurnal Ilmu Syariah, 2014)
Government  Policy  on  Islamic  Financial  Institutions  Reform  Era. Government  policies  on  Islamic financial institutions in the New Order were backgrounded in political accommodation, namely the accommodation of the Islamic academic elite within the state structure. This was used by the Islamic academic elite to broach ideas and opinions to conceive one of ideas as Islamic banking. Factors driving the process of policy formation of Islamic financial institutions was the support of policy makers, community banking, socio-cultural and juridical. Now, it so happens, that the inhibiting factors were that the policy makers were un-aspirational, public confidence in the conventional banks was still high and the lack of human resources and socialization. In the Reform era, many laws were conceived to support the development of Islamic financial institutions.DOI: 10.15408/ajis.v14i2.1280